2003
DOI: 10.1038/sj.ijo.0802312
|View full text |Cite
|
Sign up to set email alerts
|

Obesity is associated with impaired platelet-inhibitory effect of acetylsalicylic acid in nondiabetic subjects

Abstract: These data demonstrate that obese insulin-resistant subjects have a blunted response to platelet-inhibitory effect of ASA. If this blunted effect is of a single dose of ASA preserved in continuous use, it could contribute to the increased risk of atherothrombosis in insulin-resistant individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 36 publications
4
47
2
Order By: Relevance
“…Age, 4,24 sex, 4,9 cigarette smoking, 25,26 diabetes, 27,28 obesity, 29,30 and cholesterol 31,32 are reported to modify platelet responsiveness to ASA. We quantified the contribution of these cardiac risk factors to variability in platelet ASA response phenotypes and found that the total variance attributable to these factors was small.…”
Section: Discussionmentioning
confidence: 99%
“…Age, 4,24 sex, 4,9 cigarette smoking, 25,26 diabetes, 27,28 obesity, 29,30 and cholesterol 31,32 are reported to modify platelet responsiveness to ASA. We quantified the contribution of these cardiac risk factors to variability in platelet ASA response phenotypes and found that the total variance attributable to these factors was small.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is associated with a modest yet significant increase in baseline platelet reactivity. After the addition of low-dose (50-81 mg) aspirin, platelets in obese patients have more incomplete inhibition of aggregation to arachidonic acid 46,47 and higher levels of thromboxane B2. 47 These changes remained significant after accounting for potentially confounding variables including hypertension, fasting blood sugar, and hyperlipidemia.…”
Section: Obesitymentioning
confidence: 99%
“…This difference, however, was statistically marginal. Several reports suggested that older and obese patients are more prone to the development of aspirin resistance (21,22). One can suggest that ASA antiplatelet effect is more pronounced in younger patients with lower BMI or that the optimal dose of ASA is BMI-dependent.…”
Section: Commentsmentioning
confidence: 99%